Heavy metal exchangeable in an Oxisol with surface application of flue dust, aqueous lime, sewage sludge and limestone - Corrêa, Juliano Corulli; Büll, Leonardo Theodoro; Paganini, Wanderley da Silva; Guerrini, Iraê Amaral (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the soil chemical attributes and exchange of cadmium (Cd), chromium (Cr), nickel (Ni), mercury (Hg), lead (Pb) and arsenic (As) by DTPA extractor in an Oxisol with surface application of flue dust, aqueous lime, sewage sludge in rates of zero (control), 2, 4 and 8 Mg ha-1 and one additional treatment of dolomitic limestone at 2 Mg ha-1. The experiment was carried out in a randomized blocks design under field conditions, in a no-tillage system in 2003 and 2004. The surface applications of flue dust, aqueous lime and sewage sludge centrifuge and biodigestor at 8 Mg ha-1, as well as the application of limestone at 2 Mg ha-1, cause no problems of exchange to the environment, related to the heavy metals Cd, Cr, Hg, Pb, Ni and As, when applied on an Oxisol surface in no-till system. The bioavailability of heavy metals to soybean and black-oat cultures was zero, when were applied 8 Mg ha-1 sewage sludge, flue dust, and aqueous lime on soil surface in no-till system.